Experimental analysis of the multiaxial failure stress locus of commercially pure titanium at low and high rates of strain. (December 2022) - Xu, Yuan; Lopez, Maureen Aceves; Zhou, Junyi; Farbaniec, Lukasz; Patsias, Sophoclis; Macdougall, Duncan; Reed, Julian; Petrinic, Nik; Eakins, Daniel; Siviour, Clive; Pellegrino, Antonio
Highlights: A novel tension-torsion Hopkinson bar was developed. The dynamic tensile-shear failure envelope of commercially pure titanium is studied. The high-rate loading paths show proportional direct and shear strain. The Drucker-Prager criterion approximates the failure stress envelope. The failure stress locus indicates rate dependence from low to high strain rates. Abstract: The mechanical response and failure mechanism of commercially pure titanium subjected to combined tension-torsion loading are studied experimentally at strain rates ranging from 10 −3 s −1 to 10 3 s −1 . A novel tension-torsion split Hopkinson bar (TTHB) equipped with a high speed camera was utilised during high-rate experiments, while quasi-static tests were conducted using a universal screw-driven machine. The multiaxial dynamic experiments demonstrate the ability of the developed TTHB apparatus to achieve synchronisation of longitudinal and torsional waves upon loading the specimen, to satisfy the dynamic equilibrium of the specimen and to attain constant strain rate loading. The failure envelope of commercially pure titanium was analysed over a wide range of stress states including pure torsion, shear-dominated combined tension-shear, tension-dominated combined tension-shear, and plain tension. The analyses of the loading paths show that these were nearly proportional in terms of strain. The multiaxial failure stress locus was constructed in the normal versus shear stress space from experiments conducted at low and high rates of strain. The Drucker-Prager criterion was employed to approximate the failure envelope and to assess its rate sensitivity. The failure stress locus of commercially pure titanium and its rate dependence are reported for the first time. The TTHB apparatus developed allows the definition of the failure stress locus of aerospace materials directly from experiments and, therefore, the evaluation of the existing failure/yielding criteria.